Liver-specific Nr1h4 deletion in mice with human-like bile acid composition causes severe liver injury - Yusuke Mishima; Kota Tsuruya; Kinuyo Ida; Satsuki Ieda; Yutaka Inagaki; Akira Honda; Tatehiro Kagawa; Akihide Kamiya (Journal of Lipid Research)
The farnesoid X receptor, encoded by NR1H4, is crucial for bile acid, lipid, and glucose metabolism. NR1H4 mutations in humans cause a severe liver injury called progressive familial intrahepatic cholestasis 5. However, Nr1h4 deletion in mice did not cause severe liver damage at a young age, likely because of the higher levels of hydrophilic bile acids synthesized by the mouse-specific bile acid metabolic enzymes Cyp2a12 and Cyp2c70. We aimed to assess hepatic NR1H4 function by taking advantage of the recently established Cyp2a12/Cyp2c70 double-knockout (CYPDKO) mouse model, which has a human-like bile acid composition containing mainly hydrophobic bile acids. Liver-specific Nr1h4-deficient CYPDKO mice were established using an adeno-associated virus-derived genome-editing method. Nr1h4-deficient wild-type (WT) mice showed no significant changes in marker levels for serum liver injury. In contrast, Nr1h4-deficient CYPDKO mice showed an increase in the liver/body weight ratio and serum liver injury markers, suggesting that the combination of human-like bile acid composition and Nr1h4 deletion induces liver injury. Nr1h4 deletion increased total bile acid levels in the liver through the upregulation of bile acid metabolic genes and downregulation of bile acid transporters. Conversely, overexpression of a small heterodimer partner (Shp), a downstream gene of Nr1h4, suppresses liver injury induced by Nr1h4 deletion in CYPDKO mice. Overall, liver-specific Nr1h4 deficiency induced significant liver damage in mice with human-like bile acids, unlike in WT mice, validating its use as a new animal model for cholestatic liver disease. Therefore, Shp may be a potential target for the treatment of cholestasis.